ANALYSIS OF THE RELATIONSHIP BETWEEN HIGHER ORDER THINKING SKILLS AND SCIENTIFIC REASONING SKILLS IN CHEMISTRY LEARNING - Sofianto, Eko Wahyu Nur; irawati, Ratna Kartika (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2026)
Higher Order Thinking Skills (HOTS) and Scientific Reasoning Skills (SRS) play a significant role in helping students develop a comprehensive understanding of chemistry concepts. However, studies examining the relationship between HOTS and SRS remain limited. Such studies are essential for providing a theoretical foundation for the development of chemistry instruction in schools. Therefore, this study aims to analyze the relationship between HOTS and SRS in chemistry learning. This study employed a narrative literature review approach, with HOTS and SRS as the focus of the review. Relevant literature was identified through the Google Scholar database, covering publications from 2020 to 2026, using the keywords